A cost-effectiveness evaluation of the originator follitropin alpha compared to the biosimilars for assisted reproduction in Germany - Xue W; Lloyd A; Falla E; Roeder C; Papsch R; Bühler K (Dove Medical Press, 2019)
Weiguang Xue,1 Adam Lloyd,1 Edel Falla,1 Claudia Roeder,2 Rudiger Papsch,2 Klaus Bühler3,41IQVIA, Real-World Evidence, London, UK; 2Merck KGaA, Frankfurt, Germany; 3Centre for Gynecology Endocrinology & Reproductive Medicine Kinderwunsch-Zentrum Stuttgart, Stuttgart, Germany; 4Department of Gynecology, Jena-University Hospital-Friedrich Schiller University, Jena, GermanyBackground and objectives: Demand for assisted reproduction technology (ART) in Germany is high, with 100,844 treatment cycles during 2016. Many ART procedures involve ovarian stimulation with follicle stimulating hormone (FSH). Recently, biosimilar FSH products have become available. The objective of this study was to evaluate the cost-effectiveness of the recombinant FSH Gonal-f®, (Originator) in comparison to biosimilar follitropin alfa, Bemfola®, (Biosimilar 1) and Ovaleap®, (Biosimilar 2), from a German payer perspective in terms of cost per live birth.Methods: A decision tree model was developed, based on one cycle of assisted reproduction, to compare the original product to biosimilars. Clinical inputs, including live birth rates and adverse event rates were obtained from published randomized trials. Cost inputs were obtained from publicly available German sources. Clinical inputs, model structure and methodology were based on previous publications and validated by a clinical expert.Results: Results indicated that the live birth rate is higher for the Originator compared to Biosimilar 1 (40.7% vs 32.1% respectively), and Biosimilar 2 (32.2% vs 26.8%). The average cost per live birth for women treated with the Originator was estimated to be lower than those who were treated with biosimilars: Originator vs Biosimilar 1 (€10,510 vs €12,192), Originator vs Biosimilar 2 (€12,590 vs €13,606). The analysis also found that the Originator is associated with an incremental cost-effectiveness of €4,168 and €7,540 per additional live birth versus Biosimilar 1 and Biosimilar 2 respectively. Sensitivity analysis indicated probabilities of pregnancy, embryo transfer and live birth, were key drivers of model costs. Scenario analysis confirmed the robustness of the model outcomes.Conclusion: This study suggests that treatment with the Originator could result in a lower cost per live birth in comparison to biosimilars. Further analysis using real-world data, when available, is recommended to validate the results of the present study.Keywords: reproductive techniques, follitropin alfa, cost per live birth